2019
DOI: 10.3102/0034654319891400
|View full text |Cite
|
Sign up to set email alerts
|

School-, Classroom-, and Dyadic-Level Experiences: A Literature Review of Their Relationship With Students’ Executive Functioning Development

Abstract: Executive functioning (EF) is key to students’ school and lifelong success and reflects both genetic predisposition and sensitivity to negative and positive experiences. Yet there is less available literature investigating the relationship between typical experiences within school environments and student EF development. This is unfortunate, as school environments are potentially more malleable than home- or community-based factors. Thus, the purpose of this article is to present a systematic review of the lit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
31
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(33 citation statements)
references
References 131 publications
2
31
0
Order By: Relevance
“…Scholars have theorized school discipline as a critical factor that instills students with self-control (Gottfredson & Hirschi, 1990; Sameroff, 2010). Extending studies that reveal the importance of a good teacher-student relationship in the development of EF (Cumming et al, 2020; Vandenbroucke et al, 2018), this three-level meta-analysis is the first to synthesize the association between three school discipline components (i.e., structure, support, and teacher-student relationship) and self-control from preschooler to high school students. Our findings showed that school discipline is positively related to self-control, and this association is at small-to-medium effect size, according to Cohen’s (1992) benchmarks.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Scholars have theorized school discipline as a critical factor that instills students with self-control (Gottfredson & Hirschi, 1990; Sameroff, 2010). Extending studies that reveal the importance of a good teacher-student relationship in the development of EF (Cumming et al, 2020; Vandenbroucke et al, 2018), this three-level meta-analysis is the first to synthesize the association between three school discipline components (i.e., structure, support, and teacher-student relationship) and self-control from preschooler to high school students. Our findings showed that school discipline is positively related to self-control, and this association is at small-to-medium effect size, according to Cohen’s (1992) benchmarks.…”
Section: Discussionmentioning
confidence: 99%
“…We searched articles that were published up to the end of October 2018 through three electronic databases 1 : the Education Resources Information Center, PsycINFO, and PubMed with three categories of key phrases: (1) key words regarding school terms ( teach* or class* or school* or teacher-child* or teacher-student* or academic* or educat* or disciplin* or preschool* or kindergarten ), (2) key words regarding self-control terms ( self-control or self-regulation or self-discipline or effortful control or executive* or impul* or delay of gratification ), and (3) key words regarding students/children/adolescents ( adolescen* or youth* or teen* or child* or student* or pupil* ). In addition to electronic databases, we also traced the reference lists of the prior meta-analysis and systematic review of similar topic (Cumming et al, 2020; Vandenbroucke et al, 2018) and added potentially eligible studies for further coding.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although parental socialization played a relatively larger role as expected, higher school socialization, measured by the school’s ability to monitor and discipline bad behavior, was associated with higher self-control among adolescents. More broadly, reviews have shown that school and classroom environments characterized by punitiveness, low emotional support, and teacher–child conflict can inhibit the development of executive functioning that regulates impulses, decision-making, and goal-oriented behaviors (Cumming et al, 2020 ; Vandenbroucke et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…The proposed framework organises TSI into three domains reflecting distinct features of these interactions; namely, emotional support (for instance, acknowledging children's emotions and experiences, and sensitively responding to them), classroom organisation (for instance, clarifying the rules and expectations), and instructional support (for instance, asking open-ended questions) (Downer et al, 2010;Hamre et al, 2013). In agreement with the framework, numerous observational studies have shown a correlation between the quality of TSI at the classroom level (i.e., emotional, instructional, and organisational support) and children's EF/SR skills (e.g., Cadima et al, 2015b;Crockett et al, 2017;Acar et al, 2018;Goble et al, 2019; for a review, see Cumming et al, 2019). For instance, a recent meta-analysis (Vandenbroucke et al, 2017(Vandenbroucke et al, , 2018 informs further regarding the strength of the correlations between these concepts, and overall effect sizes indicate small to medium associations between TSI and working memory, and a small association with inhibition, but not cognitive flexibility.…”
Section: Introductionmentioning
confidence: 78%